Favorable Outcomes after Single Cord Blood Transplantation for Patients with High-Risk Hematologic Diseases: A Single-Institute Retrospective Analysis - Wada, Fumiya; Kanda, Junya; Watanabe, Mizuki; Arai, Yasuyuki; Hishizawa, Masakatsu; Kondo, Tadakazu; Yamashita, Kouhei; Takaori-Kondo, Akifumi (Transplantation and cellular therapy, 2021)
•RFS and GRFS of CBT significantly improved in recent years.•CBT showed better RFS than matched donor transplant in recent years.•Favorable RFS after CBT was prominent in high-risk patients.•Low relapse rates without an increase in NRM may support better outcomes after CBT. The donor selection algorithm for cord blood (CB) with regards to matched related and unrelated donors has not been fully investigated. To assess the potential of CB transplantation (CBT) in patients with hematologic malignancies, especially for high-risk patients, we performed a single-institute retrospective analysis and compared the clinical outcomes of CBT with those of HLA-matched sibling and unrelated donor transplantation. We included 394 patients aged 16 years and older with hematologic diseases who received their first allogeneic hematopoietic cell transplantation between 1990 and 2018 at Kyoto University Hospital. These included 394 recipients of single unrelated cord blood units (UCB, n = 108), HLA-matched sibling donors (MSDs, n = 143), or HLA-matched unrelated donors (MUDs, n = 143). There was no significant difference in relapse-free survival (RFS) between UCB, MSD, and MUD recipients (P = .975). However, we found a significant interaction between transplant year and CBT outcomes (P = .010), with significantly better outcomes observed in the more recent years. Furthermore, we found that CBT showed better RFS than matched donor transplantation (hazard ratio [HR], 0.50; 95% confidence interval [CI], 0.30 to 0.84). This impact was more prominent in high-risk patients (HR, 0.35; 95% CI, 0.16 to 0.77), with lower relapse rates (HR, 0.25; 95% CI, 0.11 to 0.54), and comparable non-relapse mortality (NRM) compared to matched donor transplantation. Extensive chronic graft-versus-host disease was less frequently observed in CBT (HR, 0.58; 95% CI, 0.26 to 1.28). CBT associated with favorable outcomes, particularly in high-risk patients, with good RFS and low relapse rates without an increase in NRM in the single-institute study. Although the findings should be externally validated, CBT might serve as a reasonable donor choice, particularly in high-risk patients. [Display omitted]